An investigation of the suspension characteristics of the line model of the vehicle using the Taguchi method - Stojanovic, Nadica; Jweeg, Muhsin Jaber; Grujic, Ivan; Petrovic, Miroslav; Muhsen, Sami; Abdullah, Oday I. (Zielona Góra: Uniwersytet Zielonogórski)
It can be considered that the suspension system is one of the most important systems in the VEHICLE. Where it is responsible for the stability and balance of the vehicle`s structure on the roads and curves to ensure the comfort of passengers. Also, it absorbs the shocks resulting from the unevenness of the road and prevents it from reaching the wheelhouse.
Keywords: ANOVA; vertical dynamics; MATLAB/Simulink; comfort